Never again: section 24 of the interim constitution and administrative law in South Africa - Mallet, Elisabeth Ruth (Department of Public Law, 2023)
This paper intends to explore the implications for South African administrative law of the constitutionalisation of administrative justice in the interim Constitution. It is divided into two parts, the first dealing with the impact of the constitutionalisation of the clause, and the second dealing with the impact of each specific sub-section of section 24. These sub-sections are examined in the broader context of their effect on the various factors (I have divided them into six categories) that have limited the scope of judicial review at common law before the Constitution. The analysis of the effect of section 24 will demonstrate the important (albeit limited in some respects) role that judicial review has to play in the achievement of the new democracy in South Africa, which will be discussed in general terms in Part One. Therefore, the main purpose of this paper will be to show the interaction between section 24 and broader issues of democracy. The analysis of the specific sections will illustrate how successful this interaction will be. These conclusions will be reached against the backdrop of judicial review and constitutionalism during the apartheid e~a in South Africa.